Thickness measurement using digital camera - Mohd Reedduaan, Ali (2009)
At present, some equipment in example printed solder paste thickness is measured using microscope and lighting and its accuracy is depending on operator skill. In this situation, the operator will be the main factor of the thickness measurement’s accuracy. If the operator is not skilled enough to do these jobs, then the outcome of the measurement will be very terrible. Although the operator is skilled enough, there are other factors need to be consider as a matter of fact that human will do mistake. This process can be done by installing a camera to replace the operator function. The camera will acts as a sensor, capture the image of the object, and then processed by Matrox Imaging Library (MIL) and Visual Basic 6 software. Prior to that, Calibration and Measurement Module is very essential in this project. This software was successfully developed and test result was obtained.